Going off the idea that this is 4/(y+2) - 9/(y-2) = 9/(y^2-4), let's first rewrite y^2-4 in the form of a^2-b^2, where a=y and b=2.
y/(y+2)-9/(y-2)=9/(y^2-2^2)
Now, use difference of squares: a^2-b^2=(a+b)(a-b)
4/(y+2)-9/(y-2)=9/((y+2)(y-2))
Multiply both sides by the Least Common Denominator: (y+2)(y-2)
4(y-2)-9(y+2)=9
Then keep on simplifying until you get your answer
-5y-26=9
-5y=9+26
-5y=35
y=35/-5
y=-7
Yay! Our answer is y=-7!
Answer:U.S Declaration of Independence
Step-by-step explanation:
Answer:
Logan: 17.5 Landon: 16.5
f=1.75y f =1.5y+1.5
TABLE
2|4.5
4|7.5
6|10.5
8|13.5
10|16.5
TABLE
2|3.5
4|7
6|10.5
8|14
10|17.5
Step-by-step explanation:
Read up and down
Answer:
7.88 or 7.9
Step-by-step explanation:
To find the mean, we need to do:
=> (12 + 10 + 11 + 8 + 6 + 5 + 3 + 7 + 9) / 9
=> 71/9
=> 7.88 or 7.9
I divided the sum of all numbers by 9 because we added 9 numbers.